Model Pesantren Lansia: Strategi Penguatan Psikospiritual Melalui Bimbingan Multikultural Berbasis Fiqih Keluarga - Zulfa, Nadhifatuz; Hermawan, Ambar; Maskhur, Maskhur; Abdul Aziz, Abdul Rashid (Dharmahita: Journal of Community Service and Development, 2026)
Old age is a vulnerable phase marked by declining physical, psychological, and spiritual well-being, especially when accompanied by neglect from family or social environments. This study aims to strengthen the psychospiritual condition of the elderly (integration of psychological self-awareness and spiritual growth of the elderly) through multicultural religious guidance enriched with Islamic family jurisprudence values. Using a Participatory Action Research (PAR) approach with 11 stages, the program involved 32 elderly residents of the Bojongbata Social Service Home for the Elderly (PPSLU) in Pemalang as active participants. Data collection was conducted through in-depth interviews, participatory observation, focus group discussions, and joint reflections. Initial assessments revealed that 27 out of 32 participants experienced psychospiritual issues such as anxiety, loneliness, and loss of spiritual motivation. Following the “Pesantren Lansia” (Elderly Pesantren) program intervention, there was a noticeable improvement in their religious participation, emotional stability, and self-esteem. Many resumed daily prayers, engaged in religious study groups, and expressed a sense of inner peace. This model proves effective in restoring life meaning through a contextual and compassionate spiritual approach and is recommended as a replicable model for faith-based community interventions for the elderly.